(untitled) (International Conference on Computers in Education, 2023)
This study aims to explore the impact of teacher training in the field of STEAM education on preschool teachers’ preparedness and confidence. The participants of this study were nine education and childcare professionals from a public preschool in northern Taiwan. A small-scale workshop was conducted to train the teachers, covering topics such as an overview of STEAM education, STEAM learning for preschoolers, teaching methods, and curriculum design. The results revealed that prior to the training, the teachers had a high awareness of the importance and expected outcomes of STEAM education. However, they scored relatively low in terms of teaching experience and self-efficacy. After the training, the teachers showed significant improvement in their knowledge of STEAM teaching methods and environmental support. Nevertheless, their ratings for confidence and teaching efficacy remained relatively low. These findings highlight the need for further professional development and support for teachers in the field of STEAM education. The results of this study provide valuable insights and recommendations for teacher training and instructional practices in preschool settings.